Comparison of punch biopsy and Loop Electrosurgical Excision Procedure (LEEP) on abnormal colposcopy findings in daily use which is preferable - Sastra Wianta, I Gde; Marvy Khrisna Pranamartha, Anak Agung Gde; Alexander Setiawan, William (Indonesian Journal of Perinatology, 2023)
Cervical cancer has become a global problem with high mortality and morbidity and contributed to around 311,000 deaths in 2018 which tends to rise every year. Detection of cervical cancer is very necessary to provide appropriate management to patients. Various detection and diagnosis approaches to cervical cancer continue to be developed along with advances in technology. However, comparisons of the types of methods used have not been widely reported. A biopsy is a tool used to detect a suspected malignancy that has been used for many years. One of them is a punch biopsy, a method often used to detect cervical cancer. Currently, technology is developed with the discovery of various other diagnostic tools such as Loop Electrosurgical Excision Procedure (LEEP). LEEP is an excisional procedure in high-resource settings to provide tissue for histopathology. However, the role of punch biopsy can’t be ruled out. This article discusses the differences between a punch biopsy and a LEEP procedure and the advantages and disadvantages of both.